Determination of Olive Oil Kerr Constant for Electro Optical Applications - Al-Dergazly*, Anwaar A.; Shakir, Ali A.; Abbas, Omar Adnan (Nahrain University College of Engineering Journal, 2014)
Electro optics effects are importantbranches of nonlinear optics. In thisresearch olive oil has been chosen to studyits electro optical properties. Olive oil as anorganic compound has a centro symmetricmolecular structure which means that it hasquadratic electro optical propertiesrepresented by Kerr effect. These electrooptical properties such as transmittanceversus applied voltage and birefringenceversus the square value of the appliedelectric field were measured. Theseproperties are obtained for the two types ofolive oil (virgin and refined) by analyzingof these properties, the Kerr constant andKerr coefficient for two types of olive oilhave been found at different wavelengths.